Molecular changes in Opisthorchis viverrini (Southeast Asian liver fluke) during the transition from the juvenile to the adult stage. - Aaron R Jex; Neil D Young; Jittiyawadee Sripa; Ross S Hall; Jean-Pierre Scheerlinck; Thewarach Laha; Banchob Sripa; Robin B Gasser (Public Library of Science (PLoS), 2012)
BACKGROUND: The Southeast Asian liver fluke (Opisthorchis viverrini) chronically infects and affects tens of millions of people in regions of Asia, leading to chronic illness and, importantly, inducing malignant cancer (= cholangiocarcinoma). In spite of this, little is known, at the molecular level, about the parasite itself, its interplay with its hosts or the mechanisms of disease and/or carcinogenesis. METHODOLOGY/PRINCIPAL FINDINGS: Here, we generated extensive RNA-Seq data (Illumina) representing adult and juvenile stages of O. viverrini, and combined these sequences with previously published transcriptomic data (454 technology) for this species, yielding a combined assembly of significantly increased quality and allowing quantitative assessment of transcription in the juvenile and adult stage. CONCLUSIONS: This enhanced assembly reveals that, despite the substantial biological similarities between the human liver flukes, O. viverinni and Clonorchis sinensis, there are previously unrecognized differences in major aspects of their molecular biology. Most notable are differences among the C13 and cathepsin L-like cysteine peptidases, which play key roles in tissue migration, immune evasion and feeding, and, thus, represent potential drug and/or vaccine targets. Furthermore, these data indicate that major lineages of cysteine peptidases of socioeconomically important trematodes have evolved through a process of gene loss rather than independent radiation, contrasting previous proposals.